Контроль достовірності класифікації товарів, що відносяться до «групи ризику» - Циганок, Костянтин Олексійович; Tsyhanok, Kostyantyn Oleksiyovych (Ірпінь, 2024)
Кваліфікаційна робота полягає у всебічному вивченні теоретико-методологічних та практичних аспектів контролю достовірності класифікації товарів «групи ризику» та розробці практичних рекомендацій щодо його удосконалення

The qualification work consists in a comprehensive study of the theoretical, methodological and practical aspects of control of the reliability of the classification of "risk group" goods and the development of practical recommendations for its improvement
Control of the reliability of the classification of goods belonging to the “risk group”
Keywords: митний контроль; управління ризиками; достовірність класифікації; товари «групи ризику; заниження; customs control; risk management; classification reliability; risk goods; understatement of customs duties; митних платежів